(untitled) (Ciudades, 2017)
The construction of large size residential public housing estates that took place between the Fifties and the Seventies has been replaced in the Nineties in the vast majority of the Italian cities by the physical and social rehabilitation of the former built housing estates, often characterised by degradation and negative stigmatisation. The three cases that are presented in the article describe different forms of public or public-private interventions for the integrated rehabilitation of peripheral neighbourhoods: while two of them (PRU via Artom and CdQ Sant’Eusebio) use in an innovative way some new implementation tools introduced in the Nineties – the so called “complex programmes” -, the third case (Villaggio Barona) proposes, through a small scale intervention promoted mainly by private actors, the rehabilitation of a wide and critical urban sector where the new neighbourhood becomes a new spatial and social core. Through the cases it is possible to understand not only the context of the different urban sectors, but also the interventions that have been promoted in order to foster the participation of the inhabitants, to support them and to manage and overcome the conflicts that often compromise the effectiveness of such programmes.